2014
DOI: 10.1177/1753944714531062
|View full text |Cite
|
Sign up to set email alerts
|

Aortic distensibility in bicuspid aortic valve patients with normal aortic diameter

Abstract: Regardless of the valve morphology and also in the absence of aortic dilation, aortic distensibility is impaired in BAV subjects compared with TAV subjects. This finding supports the idea of an intrinsic aortic wall anomalies underlying the impaired elasticity of the aorta in BAV patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Previous adult studies reported that aortic elasticity was not correlated with different phenotypes of BAV . Two adult studies and one pediatric study reported that the morphology of BAV seems to play a major role in the outcome of BAV disease and that the A‐P phenotype shows worse elasticity quality although the L‐R phenotype is more prone to aortic valve dysfunction .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous adult studies reported that aortic elasticity was not correlated with different phenotypes of BAV . Two adult studies and one pediatric study reported that the morphology of BAV seems to play a major role in the outcome of BAV disease and that the A‐P phenotype shows worse elasticity quality although the L‐R phenotype is more prone to aortic valve dysfunction .…”
Section: Discussionmentioning
confidence: 95%
“…Being a relatively new method, aortic elasticity may be used for this purpose in patients with BAV. Increased aortic stiffness has been observed in adults with BAV …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue dysfunction: altered stiffness and biomechanics (Nistri et al, 2002, 2008; Schaefer et al, 2007; Pees and Michel-Behnke, 2012; Oulego-Erroz et al, 2013; Warner et al, 2013; Forsell et al, 2014; Moaref et al, 2014; Petrini et al, 2014)…”
Section: Pathophysiology and Wavering Guidelinesmentioning
confidence: 99%